The Contribution of Aqidah Education to the Prevention of Juvenile Delinquency in Islamic Schools - Alfiyanto, Afif; Pranajaya, Syatria Adymas; Ikhwan, M.; NZ, Adriansyah; Hidayati, Fitri (Sekolah Tinggi Ilmu Syariah Ummul Ayman Pidie Jaya, 2024)
This study examines the contribution of aqidah education to preventing juvenile delinquency in Islamic schools through the literature review method. Aqidah education is considered necessary in shaping students' positive character, spiritual awareness, and religious identity, all of which play a role in reducing deviant behavior. Data was obtained from various relevant journal articles in the last ten years. The study results show that aqidah education effectively strengthens students' moral and ethical values, such as honesty and responsibility, and increases spiritual awareness that helps self-control. In addition, aqidah education also builds positive characters, such as discipline and empathy, and strengthens religious identities that make students more firm in Islamic principles. These findings underscore the importance of developing relevant aqidah education curricula, increasing student involvement in spiritual activities, and teacher training in teaching aqidah. Thus, aqidah education significantly prevents juvenile delinquency and forms students with character and integrity through Islamic teachings.